Ketogenic diets therapy in the management of epileptic spasms syndrome - Wang, Meng; Zhao, Fen; Sun, Lina; Yu, Yanyan; Zhang, Hongwei (Frontiers in Pediatrics, 2024)
Infantile Epileptic Spasm Syndrome (IESS) is a group of infantile spasm syndromes of various etiologies that typically present in early infancy, predispose to refractory epilepsy, and leave intellectual disability. Ketogenic diet therapy (KDT) is a non-pharmacologic treatment modality for medically refractory IESS. Recent scientific evidence supported the efficacy, safety, and tolerability of KDT for the treatment of IESS. KDT not only reduces the frequency of seizures in infants with IESS, but also improve their cognition and long-term prognosis. Recently, it has also received increasing attention as a potential treatment for neurological disorders. This reviewed the recent research progress of KDTs for the treatment of IESS, and discussed the different types and the mechanisms of KDTs, the expansion of KDT applications, the influencing factors, and future research issues.